2018
DOI: 10.1016/j.jconrel.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Implant delivering hydroxychloroquine attenuates vaginal T lymphocyte activation and inflammation

Abstract: Evidence suggests that women who are naturally resistant to HIV infection exhibit low baseline immune activation at the female genital tract (FGT). This "immune quiescent" state is associated with lower expression of T-cell activation markers, reduced levels of gene transcription and pro-inflammatory cytokine or chemokine production involved in HIV infection while maintaining an intact immune response against pathogens. Therefore, if this unique immune quiescent state can be pharmacologically induced locally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
(103 reference statements)
0
11
0
1
Order By: Relevance
“…Our group recently developed a polyurethane vaginal implant delivering the immunomodulatory drug hydroxychloroquine (HCQ) within the vaginal tract of rabbits. Our results showed that the implant was capable of attenuating pro‐inflammatory mediator production and decrease gene expression of CCR5 and CD69 in isolated vaginal mucosal T cells even after challenge with the surfactant nonoxynol‐9 . A recently published study by Lajoie et al ., presents a clinical trial on low‐risk HIV seronegative women from Nairobi (Kenya) taking either HCQ or acetylsalicylic acid orally for 6 weeks.…”
Section: Current Human Immunodeficiency Virus Epidemiologymentioning
confidence: 73%
See 1 more Smart Citation
“…Our group recently developed a polyurethane vaginal implant delivering the immunomodulatory drug hydroxychloroquine (HCQ) within the vaginal tract of rabbits. Our results showed that the implant was capable of attenuating pro‐inflammatory mediator production and decrease gene expression of CCR5 and CD69 in isolated vaginal mucosal T cells even after challenge with the surfactant nonoxynol‐9 . A recently published study by Lajoie et al ., presents a clinical trial on low‐risk HIV seronegative women from Nairobi (Kenya) taking either HCQ or acetylsalicylic acid orally for 6 weeks.…”
Section: Current Human Immunodeficiency Virus Epidemiologymentioning
confidence: 73%
“…Our results showed that the implant was capable of attenuating pro-inflammatory mediator production and decrease gene expression of CCR5 and CD69 in isolated vaginal mucosal T cells even after challenge with the surfactant nonoxynol-9. 19 A recently published study by Lajoie et al, 13 presents a clinical trial on low-risk HIV seronegative women from Nairobi (Kenya) taking either HCQ or acetylsalicylic acid orally for 6 weeks. This study showed that low-dose oral HCQ reduced systemic immune activation and oral acetylsalicylic acid is capable of reducing systemic and mucosal activated immune cells.…”
Section: Hiv Prevention Strategiesmentioning
confidence: 99%
“…Com isso foram desenvolvidos diferentes dispositivos de liberação controlada de HCQ intravaginal, de maneira a reduzir o recrutamento de células imunes submucosas, melhorar a integridade do epitélio da mucosa, diminuir a expressão de proteínas e genes de marcadores de ativação de células T e atenuar a indução de mediadores pró-inflamatórios chaves. Ambos os sistemas podem ser adequados para a prevenção da transmissão do HIV e outras infecções sexualmente transmissíveis (Chen et al, 2014(Chen et al, , 2018.…”
Section: Sistemas De Delivery E Usos Da Cq E Hcq No Tratamento De Doenças De Base Imunológicaunclassified
“…A biocompatible vaginal implant system of HCQ capable of prolonged medication release also tried in rabbits. It attenuated the protein expression of the T-cell activation marker RLA-DR (rabbit equivalent of human HLA-DR) and mRNA expression of CCR5 and CD69 on vaginal mucosal T lymphocytes [15]. HCQ-Loaded Polyurethane Intravaginal Rings also used for the prevention of HIV transmission without significant negative effect on vaginal microflora specially Lactobacilli in an in vitro study [16].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%